15.9k views
4 votes
Please help. super easy. 3x(4-8y)+3(2xy-5x)

User Orandov
by
5.2k points

2 Answers

2 votes
STEP-BY-STEP SOLUTION:

So here is the expression as displayed below:

= 3x ( 4 - 8y ) + 3 ( 2xy - 5x )

First of all, we will expand the expression as displayed below:

= 3x ( 4 - 8y ) + 3 ( 2xy - 5x )
= 12x - 24xy + 6xy - 15x

Then, we will collect like terms as displayed below:

= 12x - 24xy + 6xy - 15x
= - 3x - 18xy

After that, we will take out the common factor and factorise as displayed below:

= - 3x - 18xy
= - 3x ( 1 + 6y )

Therefore, the final answer is:

- 3x ( 1 + 6y )
User Akin
by
5.6k points
3 votes

you mean 3x(4-8y)=3(2xy-5x)?

User Manoj Chowrasiya
by
5.7k points